1975
DOI: 10.1210/jcem-40-4-601
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Weight Loss in the Evaluation of Pituitary Response to LH-RH in Women with Secondary Amenorrhea1

Abstract: Sixteen women with amenorrhea occurring in the setting of severe self-imposed weight loss and 18 women with secondary amenorrhea due to other causes were given LH-RH (luteinizing hormone-releasing hormone). Women with weight loss were found to be unresponsive to LH-RH when severely underweight. FSH responsiveness returned in a linear fashion as weight gain occurred and was not related to estrogen levels. LH responsiveness also returned with weight gain although the relationship was not linear but exponential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Changes in food intake during growth in the rat are closely correlated with changes in the size of the adipose tissue (2,14). In the human female, loss of body weight in the range of 10-15%, which corresponds to a loss of body fat of 35-40%, is associated with loss of menstrual function (10,15), and the ability to respond to luteinizing-hormone-releasing factor (16).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in food intake during growth in the rat are closely correlated with changes in the size of the adipose tissue (2,14). In the human female, loss of body weight in the range of 10-15%, which corresponds to a loss of body fat of 35-40%, is associated with loss of menstrual function (10,15), and the ability to respond to luteinizing-hormone-releasing factor (16).…”
Section: Resultsmentioning
confidence: 99%
“…In patient 2 FSH was undetectable throughout and the small FSH increase seen during the initial study did not occur. In contrast, plasma LH responses were reduced to a lesser degree by estrogen treatment and were not significantly lower on days 4 Effects of pulsatile GnRH injections in anorexia nervosa patients after weight regain Previous studies (16)(17)(18)(19) have shown that LH is secreted in a pulsatile manner, responsiveness to GnRH matures, and plasma estradiol concentrations increase, following weight regain in patients with anorexia nervosa. We therefore administered GnRH to five patients who had regained weight, but who remained amenorrhic, in an effort to determine the effects of increased endogenous estrogen concentrations on gonadotropin responses.…”
Section: Ighdmentioning
confidence: 98%
“…The individual hormone concentrations are shown for patient 14 in Fig. 5, and mean data for patients [14][15][16][17][18] are shown in Fig. 6.…”
Section: Ighdmentioning
confidence: 99%
“…Reduced food intake is known to be associated with reproductive dysfunction in humans (1,2), and rats (3)(4)(5). Several kinds of endogenous sugar acids found in rat blood have been reported to be involved in control of food intake (6,7).…”
Section: Introductionmentioning
confidence: 99%